The role of the store‐operated calcium entry channel Orai1 in cultured rat hippocampal synapse formation and plasticity - Korkotian, Eduard (J Physiol, 2016)
KEY POINTS: The role of non‐synaptic calcium entry in the formation and functions of dendritic spines was studied in dissociated cultured rat hippocampal neurons. Orai1, a store‐operated calcium channel, is found in dendritic spines. Orai1 co‐localizes in dendritic spines with STIM2 under conditions of lower [Ca(2+)]o. Orai1 channels are associated with the formation of new dendritic spines in response to elevated [Ca(2+)]o. Lack of Orai1, either by transfection with a dominant negative construct or with small interfering RNA to Orai1, results in retarded dendritic spines, an increase in density of filopodia, lower synaptic connectivity and the ability to undergo plastic changes. These results highlight a novel role for Orai1 in synapse formation, maturation and plasticity. ABSTRACT: The possible role of store operated calcium entry (SOCE) through the Orai1 channel in the formation and functions of dendritic spines was studied in cultured hippocampal neurons. In calcium store‐depleted neurons, a transient elevation of extracellular calcium concentration ([Ca(2+)](o)) caused a rise in [Ca(2+)](i) that was mediated by activation of the SOCE. The store depletion resulted in an increase in stromal interacting molecule 2 (an endoplasmic calcium sensor) association with Orai1 in dendritic spines. The response to the rise in [Ca(2+)](o) was larger in spines endowed with a cluster of Orai1 molecules than in spines devoid of Orai1. Transfection of neurons with a dominant negative Orai1 resulted in retarded maturation of dendritic spines, a reduction in synaptic connectivity with afferent neurons and a reduction in the ability to undergo morphological changes following induction of chemical long‐term potentiation. Similarly, small interfering RNA (siRNA)‐treated neurons had fewer mature dendritic spines, and lower rates of mEPSCs compared to scrambled control siRNA‐treated neurons. Thus, influx of calcium through Orai1 channels facilitates the maturation of dendritic spines and the formation of functional synapses in central neurons.